IMPLEMENTASI GAME THEORY PADA PEMILIHAN METODE PEMBELAJARAN YANG TEPAT BAGI TARUNA AAU - Pudjianto, Agus (Prosiding Seminar Nasional Sains Teknologi dan Inovasi Indonesia (SENASTINDO), 2022)
The Air Force Academy is one of the highest educational institutions in the Indonesian Air Force which is tasked with producing Indonesian Air Force officers who have good personalities, qualified academic abilities, supported by excellent physical abilities in accordance with the slogan "Tri Sakti Viaratama". In supporting learning activities, collaboration between lecturers and cadets is required to achieve learning objectives. There are 3 types of learning methods applied, namely: Conventional, Discussion and demonstration. By using game theory, it will be seen what method is most suitable to be applied in AAU.Of the three types of competition in the game above, it produces different game values ​​and strategy probabilities with varying game values. But the biggest game value, 3.68, was found in the third competition, namely between Demonstration and Conventional. This shows that the majority of respondents do not like the Discussion learning strategy. But prefers Demonstration and Conventional strategies